Innovation and sustainability: a bibliometric analysis of papers published in the International Forum Ecoinovar - Gomes, Thiago Eliandro de Oliveira; Medeiros, Flaviani Souto Bolzan; Medeiros, Natane de Cassia Leivas de; Adamy, Ana Paula do Amaral (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2016)
These days, both innovation and sustainability are widely discussed topics by society as a whole. Such debates are important so that new practices are incorporated by individuals and companies. Contributing in this sense, the International Forum Ecoinovar emerged, an event whose purpose is to promote the development of new ideas and initiatives for innovation and sustainability. Thus, this study aimed to survey the work published in the International Forum Ecoinovar the main theme innovation and sustainability in the three years 2012 to 2014. Therefore, the method used was a descriptive and explanatory research as to the purposes, adopting the technique of bibliometrics. The study findings reveal that in the three years were published 159 articles involving both issues, predominantly descriptive and qualitative research adopted in productions. In addition, we identified an increase in female participation among authors, reaching 63.28% compared 2012 to 2014. It was also found that most authors are linked to Federal University of Santa Maria, one of the event organizers, with the main network authored a composition composed of 39 members with key authors and responsible for centralizing various relationships.